2010
DOI: 10.1177/0306624x10378494
|View full text |Cite
|
Sign up to set email alerts
|

Are the “Worst of the Worst” Self-Injurious Prisoners More Likely to End Up in Long-Term Maximum-Security Administrative Segregation?

Abstract: This study examined the association of extent of prisoner self-injurious behavior (SIB) and placement in long-term maximum-security administrative segregation. A prisoner subgroup (n=132) defined by extent of SIB was matched by conviction prefix and security level to a group of prisoners who had never engaged in SIB (n=132) and compared on selected variables. Relative to prisoners who either engaged in less extensive SIB or none at all, prisoners who engaged in three or more forms of SIB while in prison were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…They also challenge existing assumptions around pathways to selfharm by identifying that committing in-prison physical violence was a far stronger predictor of self-harm in prison than either mood disorders or community violence. The role of selfharm in certain pathways to prison violence is also strongly supported in work by Lanes (2009Lanes ( , 2011, who confirms that in-prison assaults have a substantial link with self-harm.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…They also challenge existing assumptions around pathways to selfharm by identifying that committing in-prison physical violence was a far stronger predictor of self-harm in prison than either mood disorders or community violence. The role of selfharm in certain pathways to prison violence is also strongly supported in work by Lanes (2009Lanes ( , 2011, who confirms that in-prison assaults have a substantial link with self-harm.…”
mentioning
confidence: 71%
“…Paradoxically, dual-harmers are a group twice as likely to be Dual Harm: An exploration of the presence and characteristics for dual violence and selfharm behaviour in prison. 9 housed in segregation across different jurisdictions (Lanes, 2011;Kaba et al, 2014;The Correctional Investigator Canada, 2015), often due to them having engaged in in-prison violence and property destruction. The challenge for professionals is how to manage these dual risks when the assumptions and directions for their management are contradictory.…”
mentioning
confidence: 99%
“…Estimates suggest that segregation units may be up to 50 percent occupied by mentally ill inmates (Vera Institute of Justice ). Inmates with severe mental illness, particularly those who are deemed at risk of engaging in self‐injurious behavior, are also much more likely to be subjected to inmate management tools that exert strenuous force such as physical restraints for extended periods of time or Tasers to subdue behavioral outbursts (Lanes ; Lurigio ) [Multimedia Resource # 2]. A wealth of literature has accumulated on the detrimental impact of these practices on mental health (see Metzner and Fellner for review).…”
Section: Mental Illness and The Criminal Justice System In The 21st Cmentioning
confidence: 99%
“…A substantial body of correctional and critical literature supports the notion that subjecting prisoners who engage in self-injury to segregation of any form and/or physical restraints will not deter self-injury, but will instead exacerbate future acts of self-injury by reinforcing feelings of hopelessness (Arrigo & Bullock, 2008;Dear, 2006;Great Britain Parliament, 2004;Kilty, 2008b;Lord, 2008;Morin, 1999;Royal College of Psychiatrists, 2010;Toch, 2008). Not surprisingly, self-injury amongst prisoners occurs most frequently after placement in segregation (Liebling, 1994;Ross et al, 1978) and prisoners who self-injure are doubly likely to be housed in long-term segregation (Lanes, 2009b(Lanes, , 2011. Recently the OCI (2012a) concluded that close to one-third of reported self-injury incidents occur in segregation units.…”
Section: The Prison As a Contributing Factor To Self-injurymentioning
confidence: 99%
“…In fact the very authors who are credited with publishing the textual material I have selected simultaneously published their research findings in academic journals or as doctoral theses (these include: Heney, 1996;Power et al, 2013aPower et al, , 2013bPower & Smith, forthcoming). Other more recent sources of correctional discourse on self-injury have been briefly reviewed in the first chapter, namely research originating from the United Kingdom (e.g., Kenning et al, 2010;Marzano et al, 2010Marzano et al, , 2012Short et al, 2010), the United States (e.g., DeHart et al, 2009;Fagan et al, 2010;Lanes, 2009aLanes, , 2009bLanes, , 2011Smith & Kaminski, 2011),…”
Section: Materials and Data Collectionmentioning
confidence: 99%